Palmer amaranth control in established alfalfa and documentation of glyphosate-resistant Amaranthus species in Kansas - Putman, Joshua Adam (Kansas State University, 2013)
Palmer amaranth is a troublesome weed that competes for water, nutrients, and sunlight in many cropping systems throughout the United States. It is a serious production problem for alfalfa growers in the southern Great Plains region because of extended germination and impact on forage quality and yields. Glyphosate has been used extensively to control Palmer amaranth but control has become difficult. The objectives of this research were to (1) evaluate various herbicide treatments for Palmer amaranth control in established alfalfa, (2) confirm the presence and scope of glyphosate-resistance in common waterhemp and Palmer amaranth populations in eastern Kansas, and (3) to characterize glyphosate-resistance in two Palmer amaranth populations from south central Kansas. Residual Palmer amaranth control in alfalfa varied among herbicide treatments. The best late season Palmer amaranth control was accomplished with sequential treatments that included flumioxazin at 140 g ha-1 or diuron at 2,690 g ha-1 as dormant applications followed by a between cutting treatment of flumioxazin at 70 g ha-1, which was still providing 85 to 96% control in late summer. Several other treatments provided good early season Palmer amaranth control, but control diminished as the season progressed. Palmer amaranth emerges throughout the growing season and therefore, sequential herbicide treatments with good residual activity may be necessary for season-long control. Greenhouse studies indicated that glyphosate-resistant common waterhemp is present throughout eastern Kansas with several populations that survived glyphosate up to two times the suggested use rate. Glyphosate-resistant Palmer amaranth was documented in several populations collected from various counties throughout Kansas. Two populations collected in south central Kansas in 2011 survived up to eight times the typical field use rate of glyphosate. Six more populations collected in 2012 displayed similar resistance characteristics with three populations surviving up to four times the typical rate of glyphosate. Shikimate assays on susceptible and resistant Palmer amaranth biotypes confirmed resistance to glyphosate.
Keywords: Master's thesis; Agronomy (0285)